Ta’līmul Insyā Fī Tanmiyāti Kafāati At Ta’bīr At Taḥrīrī - Imam Bahroni; Nur Hadi Ihsan; Athifah Saifurrahman (Lisanudhad: Jurnal Bahasa, Pembelajaran, dan Sastra Arab, 2019)
AbstractInsya' Science is one of the writing skills in which students are taught to compose meaning and arrange it so that it can explain what is in the mind by paying attention to existing language rules, such as the rules of Naḥwu and Ṣarf and the rules of Imlā’. This science is very concerned about the ability to write which is one of the means of human interaction and is also a characteristic of humans that distinguishes it from animals, as scientists in the field of literature also prioritize writing skills. Science Insya’ also greatly influences the planting of student’s abilities in ta'bīr tahrīrī which is one of the main sciences in Arabic, where with ta'bīr tahrīrī students can study and understand what is heard and read, understand vocabulary Arabic well, uses good grammar, and composes his thoughts. Therefore, Insya’ science is taught with the aim of training students in ta'bīr tahrīrī, so that students are able to convey thoughts with good wording and with good grammar. So that, the teacher of Insya’ must know the basics in Insha’ teaching which is divided into 3 bases, namely the basics of psychology, education, and language. And the teacher must also pay attention to the main steps in Insya’ learning, such as introduction, explanation, writing elements of the paper, training, and evaluation. In addition, he must also know the problems and causes of the Insya’ learning, such as the lack of interest in students in the lesson, student’s weaknesses in Insya ', and the difficulties and obstacles faced by teachers in Insya' teaching.Keywords: Learning, Insya’, Ta'bīr Tahrīrī, Planting Ability. تعليم الإنشاء في تنمية كفاءة التعبير التحريريإمام بحران، نور هادي إحسان، عاطفة سيف الرحمنجامعة دار السلام كونتورMas.bahroni@gmail.com, nurhadiihsan@gontor.ac.id, atifahsaifurrahman@gmail.com ملخص                علم الإنشاء هو إحدى الأنشطة والمهارات الكتابية يفرض فيها إيجاد المعاني وتنسيقها بصورة تعبر عما يجول بالخاطر وخطر في الذهم اهتماما نحو القواعد اللغوية كقواعد النحو والصرف والقواعد الإملائية. ركّز على تنمية مهارة الكتابة التي تعد إحدى وسائل التواصل وكانت من خواص الإنسان التي تميزه عن الحيوان، وقد ميزها وفضلها علماء الأدب. وله أثر في تنمية القدرة على التعبير التحريري الذي يقوم بمكانة عالية بين فروع اللغة، حيث يكون فيه القدرة على الاطلاع على ما تحدث الفرد وقرأ، والتقاط المفردات واستخدام التراكيب اللغوية، والقدرة على تحديد الأفكار. فيهدف تعليم الإنشاء إلى إكساب القدرة على التعبير السليم بالأفكار والأراء المرتبة و بلغة سليمة مفردا أو تركيبا. ويجب على المدرس معرفة الأسس في تعليم الإنشاء وهي ثلاثة: الأسس النفسية، والأسس التربوية، والأسس اللغوية. كما يجب أيضا الاهتمام نحو الخطوات الأساسية في تعليم الإنشاء، وهي: التمهيد، العرض، كتابة الموضوع، الربط، والخاتمة. وكذلك، يجب عليه معرفة المشكلات وأسبابها في تعليم الإنشاء، كانصراف التلاميذ عن الإنشاء،والضعف الشائن، والقصور الشديد في إنشاء معظم التلاميذ، وإرهاق المدرسين.الكلمات الأساسية: التعليم، الإنشاء، التعبير التحريري، تنمية الكفاءة.